Content Analysis of English Textbook for 10th Grade Students Based on 2013 Curriculum - Barqiah Rahma; Andi Tenri Ampa; Syamsiarna Nappu (Institut Agama Islam Negeri Palopo, 2021)
The goal of this study is to find the description on how the materials given in the “Bahasa Inggris” textbook used in 10th grade of senior high school met the 2013 curriculum requirements, specifically in terms the suitability of contents with Core Competence and Basic Competence of 2013 Curriculum and feasibility of content of textbook. This study used mix method adopted content analysis. There are two instruments to analyze the data, researchers themselves and rubric assessment from BNSP or The Board of National Education Standard (BNES) since it used as a standardization of the textbook evaluation in 2013 curriculum. The data collected for the study were gathered from the “Bahasa Inggris” textbook used in the 10th grade of senior high school which published by Kementerian Pendidikan dan Kebudayaan in 2017 which contains 15 chapters. The finding shows that the contents of the textbook suitable with core competency and basic competency in 2013 curriculum. All chapters from the textbook meet the 2013 curriculum competency. For the feasibility of content, some materials in the textbook are not fully suitable with the requirements. In the depth and element and structure of meaning criteria, there are 2 chapters which is not fully suits the criteria required. This study found that the development of the sub-component of diversity insight does not fulfill the criteria since only two chapters have been successfully implemented. Therefore, it can be mentioned that the rubric assessment of the content feasibility of BNES complies with 75% of the materials, exercises, and text established in the textbook 'Bahasa Inggris.'